First Record of the Silverspot Squirrelfish Sargocentron caudimaculatum (Rüppell, 1838) in Mediterranean Waters - Ghanem, Raouia; Rjiba Bahri, Wafa; Chaffai, Amani; Zaouali, Jeanne; Hassen, Bilel; Karray, Sahar; El Bour, Monia; Ben Souissi, Jamila; Azzurro, Ernesto (Frontiers in Marine Science, 2022)
On 14th October 2021, a single specimen of Sargocentron caudimaculatum was captured in the locality of Cape Bon, Eastern Tunisia, by a local fisher using gillnets at 60 m depth, on rocky bottom. This observation represents the first record of this species in the Mediterranean Sea. General information on the squirrelfishes and the importance of molecular tools for the proper identification of morphologically challenging non-indigenous organisms were raised and discussed.